A Standardized Traditional Chinese Medicine Preparation Named Yejuhua Capsule Ameliorates Lipopolysaccharide-Induced Acute Lung Injury in Mice via Downregulating Toll-Like Receptor 4/Nuclear Factor-κB. (23rd March 2015) - Li, Chu-Wen; Chen, Zhi-Wei; Wu, Xiao-Li; Ning, Zhao-Xiao; Su, Zu-Qing; Li, Yu-Cui; Su, Zi-Ren; Lai, Xiao-Ping
Abstract : A standardized traditional Chinese medicine preparation named Yejuhua capsule (YJH) has been clinically used in treatments of various acute respiratory system diseases with high efficacy and low toxicity. In this study, we were aiming to evaluate potential effects and to elucidate underlying mechanisms of YJH against lipopolysaccharide- (LPS-) induced acute lung injury (ALI) in mice. Moreover, the chemical analysis and chromatographic fingerprint study were performed for quality evaluation and control of this drug. ALI was induced by intratracheal instillation of LPS (5 mg/kg) into the lung in mice and dexamethasone (5 mg/kg, p.o.) was used as a positive control drug. Results demonstrated that pretreatments with YJH (85, 170, and 340 mg/kg, p.o.) effectively abated LPS-induced histopathologic changes, attenuated the vascular permeability enhancement and edema, inhibited inflammatory cells migrations and protein leakages, suppressed the ability of myeloperoxidase, declined proinflammatory cytokines productions, and downregulated activations of nuclear factor- κ B (NF- κ B) and expressions of toll-like receptor 4 (TLR4). This study demonstrated that YJH exerted potential protective effects against LPS-induced ALI in mice and supported that YJH was a potential therapeutic drug for ALI in clinic. And its mechanisms were at least partially associated with downregulations of TLR4/NF- κ B pathways.